Advanced instrumental approaches for chemical characterization of indoor particulate matter. Issue 8 (14th September 2022) - Duarte, Regina M. B. O.; Gomes, João F. P.; Querol, Xavier; Cattaneo, Andrea; Bergmans, Benjamin; Saraga, Dikaia; Maggos, Thomas; Di Gilio, Alessia; Rovelli, Sabrina; Villanueva, Florentina
Abstract: Particulate matter (PM) is an important player of indoor air quality and a topic of great interest in terms of public health. Deciphering the complex chemical composition of indoor PM is critical to understand the association between particles components and a wide range of adverse health effects. Over the last decades, advanced analytical instrumentation has been produced capable of providing various levels of information on the chemical features of indoor PM. This article reviews the most promising of these sophisticated analytical techniques that could be employed in the identification of organic and inorganic constituents of indoor PM, including (high-resolution) mass spectrometry, organic, carbonaceous and ions analytical techniques, elemental analysis techniques such as atomic spectrometry and X-ray based methods, and surface analysis techniques. A distinction is made between online and offline instrumentation, focusing on their capabilities and how they are currently being used in the targeted and untargeted analysis of PM components. This review aims to provide the indoor air chemistry community with insights into the power of the different techniques available today, so that they can be used advantageously in future studies.